Sustainable Projects Based on the Intersection of Clean Energy with the Health Sector: A Bibliometric Review - Hugo Gaspar Hernandez-Palma; Vladimir Sousa Santos; Adalberto Ospino Castro; Angélica Jiménez Coronado; Roberto Morales Espinoza; Jonny Rafael Plazas Alvarado (International Journal of Energy Economics and Policy)
The objective of this work was to develop a bibliometric analysis of academic production related to sustainable projects based on clean, green and renewable alternative energies and their interaction with the health sector and health management on a global scale. To do this, a documentary research process based on bibliometric tools was proposed. The research is limited to the period between 2003 and 2023, executing the following search equation: (TITLE-ABS-KEY ("clean energy" ) OR TITLE-ABS-KEY ( "alternative energy" ) OR TITLE-ABS -KEY ("solar energy" ) OR TITLE-ABS-KEY ( "green energy" ) OR TITLE-ABS-KEY ( "renewable energy" ) AND TITLE-ABS-KEY ( "health sector" ) OR TITLE-ABS-KEY ( "healthcare sector" ) OR TITLE-ABS-KEY ( "public health service" ) OR TITLE-ABS-KEY ( "health management" ) ). The years with the highest production were 2020 (21), 2021 (23), 2022 (30) and 2023 (34), while the countries that have contributed the most to the topic are China (111), the USA (97) and the United Kingdom (71), which together contributed 57.76% of all publications. Of 145 sources found that published on the topic, the 18 main sources concentrate 48% of the publications. The three most cited articles were EMADIAN SM, 2017, WASTE MANAGE, WATTS N, 2018, LANCET and FULLER R, 2022, LANCET PLANET HEALTH, with a total of 1567 citations. Among the most relevant institutions in relation to the topic of study, UNIVERSITY COLLEGE LONDON stands out above all with 19 publications, followed by TSINGHUA UNIVERSITY (9) and WUHAN UNIVERSITY (8); between the three institutions they account for 20.57% of the publications found. This analysis provided critical insights for academics and professionals and underscored the relevance and dynamism of this research area in addressing clean energies and sustainable projects related with health management and health sector worldwide.